The development of the aquatic ecosystem at Krakenes Lake, western Norway, during the late glacial and early Holocene - a synthesis - Birks, HH; Battarbee, RW; Birks, HJB (KLUWER ACADEMIC PUBL, 2000)
This paper synthesises the palaeoecological reconstructions, including palaeoclimatic inferences, based on the available fossil record of plants (pollen, macrofossils, mosses, diatoms) and animals (chironomids, Cladocera, Coleoptera, Trichoptera, oribatid mites) in the late-glacial and early-Holocene sediments of Krakenes Lake, western Norway, with special emphasis on changes in the aquatic ecosystem. New percentage and influx pollen diagrams for selected taxa provide insights into the terrestrial setting. The information from all the proxies is collated in a stratigraphical chart, and the inferred changes in the lake and its catchment are discussed. The individual fossil sequences are summarised by detrended correspondence analysis (DCA), and sample scores on the first DCA axes are plotted against an estimated calendar-year timescale for comparison of the timing and magnitude of changes in assemblage composition. The DCA plots show that the large late-glacial biotic changes were synchronous, and were driven by the overriding forcing factor of temperature. During the early Holocene, however, the changes in different groups were more gradual and were independent of each other, showing that other factors were important and interactive, such as the inwash of dissolved and particulate material from the catchment, the base and nutrient status of the lake-water, and the internal processes of ecosystem succession and sediment accumulation. This multi-disciplinary study, with proxies for changes in the lake and in the catchment, highlights the dependence of lake biota and processes not only on regional climatic changes but also on changes in the lake catchment and on internal processes within the lake. Rates of change for each group are also estimated and compared. The reaction times to the sharp temperature changes at the start and end of the Younger Dryas were very rapid and occurred within a decade of the temperature change. Aquatic organisms tracked the temperature and environmental changes very closely, and are probably the best recorders of late-glacial climatic change in the fossil record.